Dietary Supplements and Popular Nutritional Strategies among Young Adults: Effectiveness, Safety, and Potential Health Risks – A Current Review of the Literature - Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Quality in Sport, 2026)
Dietary supplements and various nutritional strategies have become an integral part of young adults’ lives in recent years, a trend observed in an increasing proportion of the population. The popularity of supplementation has been rising, driven by the easy availability of preparations, the influence of social media, and the belief that health and physical performance should be supported with additional substances. However, growing attention is being paid to the inadequate regulation of the dietary supplement market and the fact that some of the preparations available online contain ingredients that do not match the manufacturer’s declaration. At the same time, there has been a marked increase in the interest in restrictive dietary strategies, such as the ketogenic diet, high-protein diet, plant-based diets, and intermittent fasting. Although these approaches may offer metabolic and performance-related benefits, they can also adversely affect the health of young adults if used improperly. The aim of this study was to present current evidence on the efficacy and safety of the most commonly used supplements and dietary strategies in the young adult population. Reports from clinical trials, observational studies and systematic reviews published between 2014 and 2024 were analyzed, with particular focus on health risks such as hepatotoxicity, electrolyte disturbances, interactions between active ingredients, and the risk of deficiencies associated with inadequately balanced diets. The available data indicate that although some supplements have a favorable safety profile, their unsupervised and combined use increases the risk of adverse effects. Similarly, many dietary patterns can be effective but require appropriate planning and, in some cases, professional supervision. These findings highlight the need for targeted health education, routine clinical assessment of supplement and diet use, and stricter regulation of the dietary supplement market.